Factors Affecting the Quality of Outpatient Registration Service and Patient Satisfaction at the Community Health Center in Surakarta and Karanganyar, Central Java - Fadhilah, Isnaini Qoriatul; Murti, Bhisma; Prasetya, Hanung (Journal of Health Policy and Management, 2020)
Background: Patient Registration Place is the first service gate at a health service facility. Community health center as primary service providers and as a place for public services must provide satisfaction to customers. This study aims to determine the factors that influence the quality of services where out-patient registration and patient satisfaction in health centers. The purpose of this study is to measure and analyze the factors that influence the quality of outpatient registration services and satisfaction.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted in Surakarta and Karanganyar health centers, Central Java, from September to October 2019. A sample of 200 patients was selected by stratified random sampling. The dependent variable was patient satisfaction. The independent variables were the qualifications of the officer, tenure, employment status, patient education, patient income, type of payment, patient age, and patient quality. The data were collected by questionnaire. The data were analyzed by a multiple logistic regression run on Stata 13.Results: The quality of outpatient registration services improved with civil servant status (OR= 4.03; 95% CI= 1.83 to 8.86; p= 0.001), patient education ≥Senior high school (OR= 0.27; 95% CI= 0.14 to 0.54; p<0.001), and BPJS insurance (OR= 0.52; 95% CI= 0.26 to 1.02; p= 0.058). Patient satisfaction improved with education level of the officer (Diploma III) (OR= 3.99; 95% CI= 1.48 to 10.68; p= 0.006), tenure ≥12 years (OR= 4.52; 95% CI= 1.74 to 11.75; p= 0.004), patient age ≥37 years (OR= 2.96; 95% CI= 1.27 to 6.84; p= 0.011), and good service quality (OR= 3.42; 95% CI= 1.40 to 8.35; p= 0.007). Patient satis-faction decreased with patient education ≥Senior high school (OR= 0.35; 95% CI= 0.14 to 0.84; p= 0.021), income ≥Rp 1,800,000 (OR= 0.39; 95% CI = 0.17 to 0.92; p = 0.031), and BPJS insurance (OR = 0.13; 95% CI = 0.05 to 0.32; p<0.001).Conclusion: The quality of outpatient registration services improves with civil servant status, patient education ≥Senior high school, and BPJS insurance. Patient satisfaction improves with education level of the officer, tenure ≥12 years, patient age ≥37 years, and good service quality. Patient satisfaction decreases with patient education, income, and BPJS insurance.Keywords: quality of patient registration services, patient satisfaction, medical recordsCorrespondence: Isnaini Qoriatul Fadhilah, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: isnainiqoriatul@gmail.com. Mobile: 089681918022Journal of Health Policy and Management (2020), 5(2): 92-102https://doi.org/10.26911/thejhpm.2020.05.02.01